A quiet place. Part II [videorecording (DVD)] - Krasinski, John, 1979-; Krasinski, John, 1979-; Blunt, Emily; Murphy, Cillian, 1976-; Simmonds, Millicent, 2003-; Jupe, Noah, 2005-; Hounsou, Djimon, 1964- (Paramount, 2021)
The Abbott family must now face the terrors of the outside world as they fight for survival in silence. Forced to venture into the unknown, they realize that the creatures that hunt by sound are not the only threats that lurk beyond the sand path.